Probing the Casimir-Polder potential with Unruh-DeWitt detector excitations - Kacper Dębski (Physics Letters B, 2021)
We investigate the Casimir-Polder physics within the simplified framework of the Unruh-DeWitt detector model mimicking the full matter-field interaction. This model is frequently used in the context of Relativistic Quantum Information theory and more recently for investigating atomic physics phenomena. Here we show that within this model an interesting relation can be shown between the excitation rate of the atom and the Casimir-Polder energy, allowing to map one onto the other, and introducing an alternative method of investigating the Casimir-Polder effect.